Menguatkan Peran Generasi Muda sebagai Agen Perubahan melalui Garda Pemuda NASDEM - Teki Prasetyo Sulaksono; Ana Mentari; Naela Faiza Khaerani; Ratri Pramudita; Rizka Maydikta (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
The young generation has a strategic role in driving social, political, and economic change in a nation. This study aims to analyze the role of Garda Pemuda NasDem as a forum for empowering the young generation of Indonesia in facing the challenges of the times and becoming agents of transformative change. With a descriptive qualitative approach, data were collected through interviews, observations, and documentation studies. The results of the study indicate that Garda Pemuda NasDem plays an active role in fostering leadership, political education, and social participation of young people through open, inclusive, and tiered cadre programs. This organization also establishes synergy with government regulations such as Permenpora and Permensos and responds to the challenge of the lack of political participation of young people with a collaborative and educational approach. Although there are still challenges to participation and effectiveness, Garda Pemuda NasDem has succeeded in creating a strategic space for the young generation to become agents of change in national development.